AB0669 12 Month Follow-up of Patient Satisfaction and Outcomes of A Novel Ankylosing Spondylitis Patient Centered Education Project. (15th July 2016) - Inderjeeth, C.A.; McQuade, J.; Johnson, C.; Briffa, K.; Edelman, J.; Cook, N.; Raymond, W.
Abstract : Background: Ankylosing Spondylitis (AS) specific patient centred interventions are rare. Following educational needs assessment, focus group consultation, and execution of a Plan, Do, Study, Act (PDSA) model, we developed and delivered a 6 weekly AS education for Ankylosing Spondylitis (AS-P) program to patients diagnosed with AS (New York criteria) Objectives: Determine participant satisfaction and response to the AS-P intervention at 12 months. Methods: Seventy-nine participants, mean age 43.5±14.5 years, diagnosed with AS were recruited for this study (AS-P). Intervention: 6-week group education program facilitated by health professionals. Program content included disease process, medication, pain management, stretches and strategies to cope with depression and fatigue. The program using patient centred approach is based on adult learning techniques and uses self-efficacy and self-management constructs. The SMAS was delivered in a small group setting delivery by interactive teaching and group discussions. The outcomes were measured post-intervention at 3, 6 and 12 months, 42 (of 79) patients completed the 12 month evaluation. Results: At 12 months, 83.3% of patient made behaviour changes after the AS-P program, predominantly, increased exercise (n=7) and lifestyle modifications (n=6), with 94.3% of these patients sustaining these changes. 69% of patients continued to set and achieve goals related to their AS. 71.4% of patients felt that the AS-P gave them all the information they required to manage their condition. 95.2% of patients felt that attending the AS-P was worthwhile. 64.3% of patients reported never forgetting to take their medication, 23.8% forgot to take their medication a couple of times a month, 4.8% forgot to take their medication most of the time, and 7.1% didn't respond. Conclusions: We have developed a program that is effective in improving patient related outcomes with high levels of satisfaction up to 12 months. Improved clinical outcomes are described in a separate abstract. The program is portable and sustainable and can be delivered in community or hospital settings. "Train the trainer program" workshops are planned for health professionals wanting to deliver this program. References: Coleman et al. (2012) A randomised controlled trial of a self-management education program for osteoarthritis of the knee delivered by health care professionals Arthritis Research & Therapy 2012, 14:R21. http://arthritis-research.com/content/14/1/R21 Disclosure of Interest: None declared